"Dirty little secret" or "Untidy quilt"? A critique of the strategic process literature - Laljani, Narendra (Cranfield University School of Management, 2005)
This literature critique forms the starting point of a research project on the development of strategic capability within the context of the realities of the strategic process. We begin by addressing the definitions of strategic process and exploring its importance. We then examine the evolution of the domain, a selection of archetypes of the strategic process, as well as some “sense-making“ devices. The role of the strategist is discussed, and we also ask if strategy-making capability is an individual or organisational characteristic. In conclusion, we examine the implications for management practice, the strengths and weaknesses of the domain, and possibilities for further research.